An overview of recent patents on oral osmotic drug delivery systems. - Kumar P.; Mishra B. (My University, 2025)
In recent years, novel drug delivery systems (NDDS) have been recognized as an attractive niche for the pharmaceutical and health industry. Among various NDDS, osmotic drug delivery systems (ODDS) are most interesting and widely applicable. Osmotic drug delivery system use osmotic pressure for controlled delivery of active agent(s). Drug delivery from these systems, to a large extent is independent of the physiological factors of gastrointestinal tract. ODDS have matured from their use with laboratory animals to most reliable controlled release systems for humans. Most of the knowledge about ODDS is found in patents, which are difficult to read, analyze and judge because of their peculiar style in which they are written. Santus and Baker reviewed ODDS patents up to year 1993; this review article gives an overview of ODDS patents from year 1994 to 2006.